The Effects of COVID-19 Risk Perception on Travel Intention: Evidence From Chinese Travelers - Meng, Yue; Khan, Asif; Bibi, Sughra; Wu, Haoyue; Lee, Yao; Chen, Wenkuan (Frontiers in Psychology, 2021)
This article seems to assess the relationship between Chinese leisure travelers’ risk perception, risk knowledge, and travel intentions of the COVID-19 pandemic in the framework of social contagion and risk communication theories. By analyzing a sample of 1209 travelers through structural equation modeling (SEM) and path analysis. We used Hayes’s process macro to analyze the moderation effects of age, gender, and education between risk perception, media and interpersonal communication, and risk knowledge. It is found that travelers’ were more concerned about self-efficacy than severity. Travelers' risk perception predicts tourists' information-seeking process. This process helps travelers to accumulate risk information that influences their travel intentions. Travelers give more importance to interpersonal (contagion) communication in making a traveling decision. Demographic factors influence traveling decision-making; females travelers were found more risk resilient than men. Young travelers seek information at low and old at high-risk levels. Marketing implications are provided.